Impacts of psychological capital on the ethical behavior of teachers: a case of educational sector in Pakistan - Rehman, Fazal ur; Md Yusoff, Rosman Bin; Mohamed Zabri, Shafie Bin; Ismail, Fadillah Binti (EDP Sciences, 2018)
This study aims at investigating the effect of psychological capital on the ethical behavior of teachers in the higher educational sector of Pakistan. This study applied quantitative approach to collect data through questionnaire based survey from the teaching staff of Rawalpindi and Islamabad region universities in Pakistan. This study used descriptive statistics and step wise regression to analyze the collected data. Results of the study indicate that psychological capital has positive and statistically significant effect on the ethical behavior of teachers in the higher educational sector of Pakistan. This study addresses the need to investigate the relationship of psychological capital with the ethical behavior of teachers in the higher educational sector of Pakistan, which can help in understanding the nature of these variables in the higher educational sector of Pakistan.